The Development of A Database Program for Fatal Electrocution and Fatal Fall Accidents in Construction Industry - Emmidia Djonaedi; Chia-Fen Chi; Fauzia Dianawati; T.Yuri Zagloel (International Journal of Technology, 2014)
Classifying accident information into a specific categories provides inspectors with data needed for accident analysis and subsequent decision-making. This research proposes development of a database for accident analysis prevention. It will also presents a template and accident database focusing on fatal electrocutions and falls in the construction industry. Data has been stored in MySQL database, and a program editor has been employed to customize the program for accident analysis. An accident analysis form connected to the database has been developed, along with an accident report in qualitative format and meaningful categories to provide analyzable data. The program can be used as soon as an inspector finishes preparing an accident report; accessing the database minimizes the lead time for translating qualitative reports into analyzable data, so that the Council for Labor Affairs, corporate personel, and inspectors can have real time information about accident trends and patterns for the prevention of repetitive accidents.